Disaster Mitigation Measures as Strategies of Disaster Risk Preparedness in Informal Settlements of Nyeri Town, Nyeri County, Kenya - Muriuki, Zachary K; Kei, Robert; Muchiri, John Munderu (European Journal of Health Sciences, 2022)
Purpose: The main objective of this study was to examine disaster mitigation measures as strategies of disaster risk preparedness in informal settlements of Nyeri town, Nyeri County, Kenya. To achieve this, the study was guided by two specific objectives: To identify the role of stakeholders in disaster management in the informal settlements of Nyeri Town and to determine the challenges encountered during disaster risk reduction initiatives in the informal settlements of Nyeri Town. Methodology: The study adopted a descriptive research design using primary data collected through a structured questionnaire. The population for this study was 384 respondents of the four settlements of Nyeri town, that is, Majengo Witemere Ngangarithi, Mathari and Ruring'u Muslim village. The study used a sample of 384 respondents that was divided proportionally between the four settlements. Findings: The study found out that, majority of the respondents [93.0%] was aware of the disasters that can affect them in their area of residents. The study further established that, majority of the residents 196 (51.0%) were aware of the existence of disaster risk reduction policies as compared to 49.0% who were not aware of any disaster risk reduction policy. The results also showed that there was a significant association between the level of education of the respondents and the level of awareness of the disaster that could affect them [X2 (3) = 14.848, p-value =0.002<0.05] and the religions of the respondents and the level of awareness of the disaster that could affect them [X2 (2) = 7.090, p-value =0.029<0.05]. The results however indicated that, there was no significant association between the level of awareness of the disaster that could affect the respondents with the area of residents, age of the respondents and their occupation as given by the p-values of 0.393, 0.485 and 0.390 respectively. The study further established that, there was a significant association between the education level of the respondents and the level of awareness of any policy rule concerning with disaster risk reduction [X2 (3) = 8.056, p-value =0.045<0.05], and the religions of the respondents and the level of awareness of any policy rule concerning with disaster risk reduction [X2 (2) = 10.031, p-value =0.007<0.05]. It was concluded that Risk assessment as a step for successful disaster reduction measures will ensure that the community members are aware of the possible hazards. National and County government should incorporate the national and international policies and guidelines in their policy. Recommendations: The Government should be keen on learning on previous disasters that have affected other informal settlements and other parts of the country by having disaster management well kwon by the communities living in informal sectors. The researcher further recommends to the scholars to consider research on Disaster risk preparedness as the strategy of counties development agenda and Social and economic potentials that the County Governments can tap in informal settlements.